TRAJECTORIES AND CHALLENGES. THE CHALLENGE OF GREENING AND INSTITUTIONALIZING CLIMATE CHANGE IN HIGHER UNIVERSITY EDUCATION - Canaza-Choque, Franklin Américo (2021)
The purpose of this study is to carry out a preliminary tour of the different purposes that the Peruvian university has set since the replica of institutionalizing the environmental issue was implemented, and later, that of installing Climate Change (CC) in its deepest structure as the main challenge in the field of Higher Education (SE). This is clear, without before, dimensioning the environmental issue in its substantive operations and consolidating Sustainable Development (SD) inside and outside its space. In this journey, part of the theoretical-documentary analysis that takes into account the tensions faced inside and outside the university model is used. The results show a special emphasis on the tendencies to green the University Higher Education (ESU), a challenge of the first term that has not finished when defining its objectives. However, although this preparatory scenario was important to further delineate adaptive measures against CC in the substantive functions of the university. Currently, that challenge must be overcome. For this, it will not only be necessary to consolidate an Environmental Education (EA) and SD or to calibrate environmental efforts in the attempt to attenuate global tension, but also to find a more sustainable university model and, at the same time, to neutralize the CC impact. Keywords: climate change – environment – higher education – sustainable development – universities